Hydrogen Peroxide Can Enhance the Synthesis of Bioactive Compounds in Harvested Broccoli Florets - Duarte-Sierra, Arturo; Thomas, Minty; Angers, Paul; Arul, Joseph (Frontiers in Sustainable Food Systems, 2022)
Hydrogen peroxide (H2O2) is a reactive oxygen species (ROS) which participates in the signal transduction responses of plants towards biotic and abiotic stresses. Therefore, the objective of this study was to link the exposure of low doses of H2O2 to the improvement of the phytochemical composition of broccoli florets, in particular the content of glucosinolates (GLS), and hydroxy-cinnamates (HCA) without affecting the quality parameters of the vegetable. A dose of 1.25 mM H2O2 applied for 180 min was effective (hormetic) in maintaining the color of broccoli florets, which was also compared with a higher dose of 5.0 mM H2O2 applied for 180 min. The intensity of the treatments was related to respiration rate, which was monitored for 21 d at 4 °C along to weight loss. The initial respiration rate of florets exposed to both doses of H2O2 was significantly (p<0.0001) higher relative to controls and resulted in weight loss in florets treated with the hormetic dose. The antioxidant capacity of florets, measured indirectly as Oxygen Radical Absorbance Capacity (ORAC) and ascorbic acid (AA), decreased in florets exposed to both doses. The concentration of glucobrassicins, aliphatic GLS, and HCA was consistently higher in florets treated with the two doses, compared to non-exposed florets. The enhancement of these compounds was accompanied by the over expression, immediately (6 h) after treatments, of tryptophan N-hydroxylase 2 (CYP79B3), dihomomethionine N-hydroxylase (CYP79F1), and phenylalanine ammonia-lyase (PAL) genes. Overall, the tested doses of H2O2 positively influenced the augmentation of indole-type and aliphatic GLS, as well as HCA in broccoli florets.